2007
DOI: 10.1097/fpc.0b013e3280120043
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of the 5-lipoxygenase biosynthetic pathway and variable clinical response to montelukast

Abstract: The overall mean response to montelukast may be skewed towards a response phenotype by a small subset (<15%) of asthma patients. CYSLTR2 and ALOX5 polymorphisms may predispose a minority of individuals to excessive cysteinyl-leukotriene concentrations, yielding a distinct asthma phenotype most likely to respond to leukotriene modifier pharmacotherapy. These findings require replication to establish validity and clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 51 publications
3
81
5
Order By: Relevance
“…The other four published studies could not reproduce these findings (144,145,147,148). As these results were obtained in different populations and using different end points, this suggests that, although not sufficient to explain the variation in patient response to LTRAs, this polymorphism is a strong candidate and is potentially exerting its influence with other gene polymorphisms.…”
Section: Lt Pharmacogeneticscontrasting
confidence: 42%
See 2 more Smart Citations
“…The other four published studies could not reproduce these findings (144,145,147,148). As these results were obtained in different populations and using different end points, this suggests that, although not sufficient to explain the variation in patient response to LTRAs, this polymorphism is a strong candidate and is potentially exerting its influence with other gene polymorphisms.…”
Section: Lt Pharmacogeneticscontrasting
confidence: 42%
“…Another study found no polymorphism specific bronchodilator responses between homozygous wildtypes and heterozygotes for the ALOX5 Sp1 polymorphism in 52 asthma subjects (143). Kim et al found no significant association between LTRA requirement and polymorphisms in the ALOX5 gene and Klotsman et al identified an 18-25% improvement in peak expiratory flow for mutant alleles of ALOX5 SNP rs4987105 and rs4986832 (p = 0.01 for both), whereas wild-type patients only showed a 10% improvement (144,145). These data illustrated that genes regulating the expression of LTs could influence the efficacy of therapeutics that target their synthesis and/or activity and further studies are required to determine the role of ALOX5 polymorphisms on these responses.…”
Section: Lt Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study by Lima et al found that patients carrying 5 tandem repeats had an increased risk of exacerbations compared to patients carrying variant alleles [57]. Studies by Fowler et al and Klotsman et al reported no increased risk of poor montelukast response in patients carrying this genetic variant [54,58]. The effect of the ALOX5 promotor SP1 tandem repeat variant on treatment response seems to be context specific and may depend on the specific (non-5 tandem repeat) variant [59].…”
Section: Leukotriene Modifiers Responsementioning
confidence: 57%
“…Initially, candidate-gene studies on LTRA response focused on genes within pharmacological leukotriene pathway, such as leukotriene A4 hydrolase (LTC4s), 5-lipoxygenase (ALOX5), leukotriene A4 hydrolase (LTA4H), and cysteinyl leukotriene receptor 1 (CysLTR1) [41]. In addition, genes influencing LTM pharmacokinetics such as CYP enzymes (CYP3A4, CYP2C9) and transporter genes (SLCO2B1, MRP1/ ABCC1) have also been investigated [53,54]. A recent systematic review showed that despite a large amount of pharmacogenetics LTRA studies; only variants in two genes, ALOX5 and MRP1, have been replicated to show similar outcomes of LTRA response at least once [41].…”
Section: Leukotriene Modifiers Responsementioning
confidence: 99%